Improved education in the student environment towards the industrial revolution 4.0 - Ismayadi; Silvia, Desy; Putra, Rachman Mega; Azuga, Nabila Afifah; Candra, Ade Ary; Kristiando (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2019)
Real work lecture is a form of activity carried out by a college of community service activities in a certain area or an educational institution. provide real work experience in the field in the field of forming an independent attitude and responsibility in the implementation of work and activities in the field. In addition, KKN also aims to assist the community in improving their level of knowledge and skills so that it is expected to improve the welfare of the people in the area. KKN activities run well and smoothly. This is due to the enthusiasm of the community including the children there who are passionate about participating in every activity we carry out. The activities carried out at namely the socialization of the importance of education, the socialization of the importance of risk behavior, the mastery of Indonesian Language Mastery in Era 4.0, tutoring and discussion, and the river of life. It is hoped that the implementation of the Community Service programs can be useful and applied in the lives of all parties concerned.